Channa rara, a new species of snakehead fish from the Western Ghats region of Maharashtra, India (Teleostei: Labyrinthici: Channidae) - Britz, Ralf; Dahanukar, Neelesh; Anoop, V.k.; Ali, Anvar (Zootaxa, 2019)
Channa rara, new species, is described from the Jagbudi River in Maharashtra, India. It belongs to the Gachua group and differs from all its members by the possession of one or more ocelli in the posterior part of the dorsal fin in adults (vs. ocelli absent or 1, rarely 2–3 ocelli in juveniles only). It is further distinguished from most species of the C. gachua group by having 6–7 dark concentric bands on the pectoral fins. We review recent descriptions of species of the genus Channa and conclude that C. royi is a synonym of Channa harcourtbutleri, that the diagnosis of C. shingon from C. harcourtbutleri is seriously flawed and that C. torsaensis is not sufficiently diagnosed from C. quinquefasciata. The recently described C. amari is a junior synonym of C. brunnea.